2017
DOI: 10.1016/j.jacc.2017.08.050
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic Value of Cardiac Magnetic Resonance Tissue Characterization in Risk Stratifying Patients With Suspected Myocarditis

Abstract: CMR tissue characterization provides effective risk stratification in patients with suspected myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
263
4
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(314 citation statements)
references
References 34 publications
14
263
4
15
Order By: Relevance
“…The major cardiac event rate of almost 50% was markedly increased compared with cases of myocarditis in broad populations. For example, among 670 patients admitted to hospital with myocarditis unrelated to ICI, a fulminant course was noted in 15% of patients (29,30). An additional difference is that, in our cohort, 38% of patients who had a fulminant course had a normal LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…The major cardiac event rate of almost 50% was markedly increased compared with cases of myocarditis in broad populations. For example, among 670 patients admitted to hospital with myocarditis unrelated to ICI, a fulminant course was noted in 15% of patients (29,30). An additional difference is that, in our cohort, 38% of patients who had a fulminant course had a normal LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of these CMR criteria has a sensitivity of 76% and specificity of 96% for myocarditis . CMR has also shown to be an effective tool for risk stratification and prognostication in general cases of myocarditis . Despite the potential benefits of CMR, its limited availability and the difficulty in obtaining this relatively lengthy test in severely ill patients are major obstacles that restrict its widespread use in every patient with suspected myocarditis.…”
Section: Managementmentioning
confidence: 99%
“…Recent studies have demonstrated the prognosis in the individual diagnostic categories like myocarditis and Takotsubo cardiomyopathy. (19)(20)(21) However, there is no evidence in the literature on the prognostic significance of the CMR findings and conventional risk factors in MINOCA. The only study which looked at mid-term mortality was by Mittal et al (22) However, they looked at patients presenting via the primary percutaneous coronary angiography pathway with non-obstructed coronaries.…”
Section: Introductionmentioning
confidence: 99%